2015
DOI: 10.4103/0019-5049.156878
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia for awake craniotomy: A retrospective study of 54 cases

Abstract: Background and Aims:The anaesthetic challenge of awake craniotomy is to maintain adequate sedation, analgesia, respiratory and haemodynamic stability in an awake patient who should be able to co-operate during intraoperative neurological assessment. The current literature, sharing the experience on awake craniotomy, in Indian context, is minimal. Hence, we carried out a retrospective study with the aim to review and analyse the anaesthetic management and perioperative complications in patients undergoing awake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 24 publications
1
16
0
2
Order By: Relevance
“…Data of the study characteristics are shown in Table 1 . A total of fourteen case series [ 10 , 17 , 19 , 20 , 23 , 28 , 39 , 41 , 44 , 47 , 51 , 53 , 54 , 60 ] thirteen prospective studies [ 18 , 21 , 22 , 25 27 , 30 , 33 , 35 , 38 , 52 , 55 , 61 ], seventeen retrospective studies [ 24 , 29 , 31 , 34 , 37 , 40 , 42 , 43 , 45 , 46 , 48 50 , 57 59 , 62 ], two RCTs [ 32 , 56 ], and one pseudo-RCT [ 36 ] comprising 5945 AC procedures in 5931 patients were analysed ( Table 1 ). Of note, during the data extraction process it appeared that nine studies [ 20 , 22 , 27 , 31 , 42 46 ] partially repor...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Data of the study characteristics are shown in Table 1 . A total of fourteen case series [ 10 , 17 , 19 , 20 , 23 , 28 , 39 , 41 , 44 , 47 , 51 , 53 , 54 , 60 ] thirteen prospective studies [ 18 , 21 , 22 , 25 27 , 30 , 33 , 35 , 38 , 52 , 55 , 61 ], seventeen retrospective studies [ 24 , 29 , 31 , 34 , 37 , 40 , 42 , 43 , 45 , 46 , 48 50 , 57 59 , 62 ], two RCTs [ 32 , 56 ], and one pseudo-RCT [ 36 ] comprising 5945 AC procedures in 5931 patients were analysed ( Table 1 ). Of note, during the data extraction process it appeared that nine studies [ 20 , 22 , 27 , 31 , 42 46 ] partially repor...…”
Section: Resultsmentioning
confidence: 99%
“…Three studies continued conscious sedation with propofol in a reduced dosage also during the awake phase [ 18 , 32 ], and the awake anaesthesia management is unknown for six studies [ 19 , 35 , 55 , 58 , 61 , 62 ]. Dexmedetomidine (around 0.1–0.7 μg kg -1 h -1 ) was continued in totally 36 procedures during the "awake" phase [ 48 , 59 , 60 ]. It could be shown, that dexmedetomidine has a minimal interference with electrocorticography (ECoG) during AC in a dosage of 0.2–0.5 μg kg -1 h-1 [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations